Differential identification of Mannheimia haemolytica genotypes 1 and 2 using colorimetric loop-mediated isothermal amplification - Rohana P. Dassanayake; Michael L. Clawson; Fred M. Tatum; Robert E. Briggs; Bryan S. Kaplan; Eduardo Casas (BMC Research Notes, 2023)
Abstract Objective Mannheimia haemolytica is the primary bacterial pathogen associated with bovine respiratory disease complex (BRDC). While M. haemolytica has been subdivided into 12 capsular serotypes (ST), ST1, ST2 and ST6 are commonly isolated from cattle. More recently, M. haemolytica strains isolated from North American cattle have been classified into genotypes 1 (ST2) and 2 (ST1 and ST6). Of the two genotypes, genotype 1 strains are frequently isolated from healthy animals whereas, genotype 2 strains are predominantly isolated from BRDC animals. However, isolation of both genotypes from pneumonic lung samples can complicate diagnosis. Therefore, the aim of this study was to develop a colorimetric loop-mediated isothermal amplification (LAMP) assay to differentiate M. haemolytica genotypes. Results The genotype specificity of the LAMP was tested using purified genomic DNA from 22 M. haemolytica strains (10 genotype 1, 12 genotype 2) and strains from four related Pasteurellaceae species; Bibersteinia trehalosi, Mannheimia glucosida, Pasteurella multocida, and Histophilus somni. Genotype 1 (adhesin pseudogene B1) specific-LAMP reactions amplified DNA only from genotype 1 strains while genotype 2 (adhesin G) reactions amplified DNA only from genotype 2 strains. The overall detection sensitivity and specificity of the newly developed colorimetric LAMP assay for each genotype were 100%. The limits of detection of two LAMP assays were 1–100 target gene copies per reaction. LAMP primers designed in this study may help the differential identification of M. haemolytica genotypes 1 and 2.